Evaluating and ranking infrastructure manager strategies using the combined AHP/DEA method - Kecman, Pavle; Jovanović, Predrag; Bugarinovic, Mirjana (Univerzita Pardubice, 2010)
Restructuring of European Railway companies has resulted in creating new subjects within railway systems - infrastructure managers (IM) on the one hand and railway operators on the other. Each of these subjects strives for efficient operation within the boundaries dictated by regulatory bodies or government directly. In this paper we examine the efficiency and rank different business strategies of railway infrastructure managers using combined AHP/DEA method. Different strategies include different number of paths allocated (diferent capacity utilization index), different ratio of paths allocated to passenger and freight trains in case of demand for paths being higher than the capacity of the line and infrastructure access charges based on different principles. Each strategy examined is subjected to constrains such as the maximum capacity of the line and public service obligation considering the obligatory number of passenger trains in the timetable defined by the public authorities. The method applied for evaluating and ranking different strategies is a combined AHP/DEA method. Each strategy of the IM is regarded as a decision making unit (DMU) and as such, in the first stage of the model, paired with each of the remaining DMU’s. The Data Envelopment Analysis (DEA) is run for each pair of units separately. In the second stage, the pair wise evaluation matrix generated in the first stage is utilized to rank scale the units via the Analytical Hierarchical Process (AHP). The results can be used for evaluation of efficient use of infrastructure capacity and financial efficiency of IM simultaneously.
Keywords: infrastructure manager; evaluating; ranking; AHP/DEA